Improvement of artemisinin content through mutation of in vitro shoot cultures of Artemisia cinamedicinal plant - Aryanti . (Indonesian Journal of Pharmacy, 2011)
Improvement of plant traits through mutation induction of herbal medicine of  shoots  Artemisia  cina  in  vitro  have  conducted  by  gamma  rays.  About  200  of A.cina shoots in vitro were cultured in Murashige & Skoog(MS) medium without phyto-hormone  were  irradiated  by  the  dose  of  10  Gy  at  Gamma  Chamber  in PATIR – BATAN. Irradiated shoot cultures were then multiplication and selected. The selected mutant lines have acclimatized and cultivated at distance of 0.5 x 1 m  at  Bogor  region.  21  of  mutant  lines  have  been  obtained  from  630  A.cina mutant  lines  from  field  cultivation.  The  morphological  observation  i.e.,  leaves area,  plants  high  and  percentage  of  flower  emerge  have  conducted  when  the plants  were  cultivated  in  the  field.  The  artemisinin  content  of  mutant  lines  and original plant have conducted by using  HPLC. The result  shown  that the mutant lines  had  higher  leaves  area  than  original  plant  and  some  of  mutant  lines  were shorter  than  original  plant.  The  percentage  of  emerge  flowers  were  reached 50.17%  to  be  A31.1  mutant  line.  The  improvement  of  plant  traits  by  gamma rays  was  showed  by  increasing  of  artemisinin  in  A.cina  mutant  lines.  The highest  artemisinin  content  to  be  A32a2,  A32c1  and  A36.2  were  found 21.03  mg/g, 19.99 and  15.79  mg/g  respectively  compared  to  the original  plant only 0.40 mg/g. The improvement of artemisinin  content of mutant line A32a2, A32c1 and A36.2 were 52.25; 48.97 and 38.48% respectively.Key word :mutation, shoots in vitro, artemisinin, Artemisia cina